Determinantes de la Tasa de Cambio Nominal: Verificación Empírica del Modelo de Precios Rígidos en la Economía Colombiana, 1995:I–2006:I (2007)
First at all, this paper shows the relevant characteristics of different models that are been created throughout the history in order to explain the nominal exchange rate’s behavior. Second, it is done an econometric exercise of the sticky–price nominal exchange rate model on the Colombian economic, through the cointegration technique. From the empirical exercise is found that the relevant variables implied in the sticky–price nominal exchange rate model form a stable long term relationship and the estimated elasticities’ sing confirm the model.